Time dynamics of the Bacillus cereus exoproteome are shaped by cellular oxidation - Madeira, Jean-Paul; Alpha-Bazin, Béatrice; Armengaud, Jean; Duport, Catherine (Frontiers in Microbiology, 2015)
At low density, Bacillus cereus cells release a large variety of proteins into the extracellular medium when cultivated in pH-regulated, glucose-containing minimal medium, either in the presence or absence of oxygen. The majority of these exoproteins are putative virulence factors, including toxin-related proteins. Here, B. cereus exoproteome time courses were monitored by nanoLC-MS/MS under low-oxidoreduction potential (ORP) anaerobiosis, high-ORP anaerobiosis, and aerobiosis, with a specific focus on oxidative-induced post-translational modifications of methionine residues. Principal component analysis (PCA) of the exoproteome dynamics indicated that toxin-related proteins were the most representative of the exoproteome changes, both in terms of protein abundance and their methionine sulfoxide (Met(O)) content. PCA also revealed an interesting interconnection between toxin-, metabolism-, and oxidative stress–related proteins, suggesting that the abundance level of toxin-related proteins, and their Met(O) content in the B. cereus exoproteome, reflected the cellular oxidation under both aerobiosis and anaerobiosis.